影片案例導向學習系統對於實習生科技知能發展影響之研究 Effects of a Video-Based Case Learning System on Developing Technology Integration Competencies of Student Teachers - 張雅芳 Ya-Fung Chang; 徐加玲 Chia-Ling Hsu (National Taiwan Normal University, 2013)
為探究影片案例導向學習（video-based case learning, VBL）系統對於實習生科技融入教學知能發展的影響，本研究將57 位實習生分為實驗組與對照組，實驗組使用VBL 系統並且參與線上討論，對照組則沒有。實習生在實習開始與結束時接受科技知能問卷調查，實習結束後，實驗組另外接受焦點訪談。結果有如下發現：一是實習生認為學科教學知識在實習期間有顯著的成長，反映在學科教學科技知識上也有成長；二是實驗組與控制組在科技知能成長上並沒有顯著的差異；三是電腦技能自評較好的實習生比起較差者有顯著的科技知能成長；四是實習生肯定VBL 系統在教學實務上的價值。最後本研究針對VBL 系統的設計與實施、科技知能的發展途徑，以及未來的研究提供相關建議，庶幾有助於實習生持續發展科技知能。 The purpose of this study was to examine the effects of a video-based case learning (VBL) system on developing technology integration competencies of student teachers. Overall, 52 student teachers were divided into 2 groups, (i.e., experimental and control groups). The experimental group was assigned to use the VBL system and participated in on-line discussion forums; the control group followed a regular schedule without using the VBL system. All student teachers completed questionnaires regarding their technology integration competencies at both the beginning and end of the course. At the end of the course, focus group sessions were arranged for the experimental group to discuss their personal experiences and gains from using the VBL system. The main results of this study are as follows: (1) student teachers' pedagogical content knowledge grew substantially during their internships, which resulted in improved technological pedagogical content knowledge; (2) no significant difference was exhibited in the improvement of technology competencies between the experimental and control groups; (3) student teachers who possessed high computer-skill ratings exhibited a significantly higher growth in technology competencies than did students who possessed low computer-skill ratings; and (4) student teachers appreciated using the VBL system for improving their teaching practices. Finally, this study provides relevant suggestions regarding upgrading and implementing a VBL system, strategies for developing technology competencies, and future research directions that might help continuously develop the technology competencies of student teachers.